2019
DOI: 10.1149/2.0391902jes
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electrolyte Solvents at Solid/Liquid Interface Using Gap-Mode Surface-Enhanced Raman Spectroscopy

Abstract: Understanding the aprotic solution structures at the immediate vicinity of solid/liquid interface (SLI) is critically important for next generation lithium ion battery development. Yet, it is still challenging to investigate the carbonate chemical profiles close to the diffuse layer (about 10 nm) of the electrical double layer at SLI due to the lack of a ultrahigh surface sensitive tool. In this work, we demonstrate the structures of commonly used carbonate solvents (ethylene carbonate (EC) and diethyl carbona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…Specifically, the peaks at 729 and 2245 cm -1 were ascribed to OCO ring breathing of FEC and CN stretching vibration of ADN, respectively. [46][47][48] The characteristic peaks of ADN and FEC mentioned above were shifted to higher frequencies in DSPE-2M, indicating the strengthening Li + -FEC and Li + -ADN coordination. [46][47][48] Previous studies have shown that nitriles are incompatible with LMAs.…”
Section: Resultsmentioning
confidence: 92%
“…Specifically, the peaks at 729 and 2245 cm -1 were ascribed to OCO ring breathing of FEC and CN stretching vibration of ADN, respectively. [46][47][48] The characteristic peaks of ADN and FEC mentioned above were shifted to higher frequencies in DSPE-2M, indicating the strengthening Li + -FEC and Li + -ADN coordination. [46][47][48] Previous studies have shown that nitriles are incompatible with LMAs.…”
Section: Resultsmentioning
confidence: 92%
“…Many techniques have been been developed to probe the nature of the electrochemicallygenerated SEI, with recent progress characterizing the ratio and spatial location of organic and inorganic species via neutron reflectivity (NR), 3 X-ray photoelectron spectroscopy (XPS), [4][5][6] scanning spreading resistance microscopy (SSRM) and time-of-flight secondary ion mass spectrometry (ToF-SIMS), 7,8 , surface-and tip-enhanced Raman spectroscopy (SERS and TERS), 9,10 and classical molecular dynamics/quantum chemical calculations. 11 These studies are coming to a consensus that the initial SEI formation under electrochemical bias involves primarily organic species from electrolyte reduction, which under further cycling becomes thinned at the expense of inorganic phases such as lithium silicates (Li x SiO y ), lithium oxide (Li 2 O), lithium peroxide (Li 2 O 2 ), lithium hydroxide (LiOH), and lithium carbonate (Li 2 CO 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, turning to operando SERS shown in Figure 1 b, we clearly observe a potential-dependent growth of the EC+Li + peaks during negative polarization of the Au, which can be explained by the charging of the electric double layer and accumulation of Li + and solvation of EC at the SERS substrate surface. The intensities of the respective peaks can be extracted by fitting, and Figure 2 a shows that the EC+Li + peaks clearly increase in intensity, whereas the EC peaks remain constant until ∼2.3 V. On the basis of the EC+Li + to EC peak area ratio, a Li + concentration at the Au surface can be estimated (according to the relationship derived by Yang et al 16 ) and was found to increase from the expected 1 M at the OCP up to 1.5 M at 2.3 V vs Li + /Li (see SI section S3 for details). However, all of the peaks associated with the electrolyte decrease in intensity thereafter because of SEI formation.…”
mentioning
confidence: 97%